Women and leadership in a policing context - Anthony, Mary Philomena (Curtin University, 2015)
This research examines the lived experiences of middle to top level American and Australian policewomen to identify the reasons for their paucity in key senior leadership positions and the challenges faced by them in seeking leadership roles. Data was collected using a qualitative research methodology (in-depth interviews) and analysed using an interpretivist approach. A major finding of this study is that policewomen question their own leadership aspirations, which lends a new meaning to leader identity.